Knowledge-Based Systems in Biomedicine and Computational Life Science - Pham, Tuan D.; Jain, Lakhmi C. (Studies in Computational Intelligence,, 2013)
This book presents a sample of research on knowledge-based systems in biomedicine and computational life science. The contributions include: ·         personalized stress diagnosis system ·         image analysis system for breast cancer diagnosis ·         analysis of neuronal cell images ·         structure prediction of protein ·         relationship between two mental disorders ·         detection of cardiac abnormalities ·         holistic medicine based treatment ·         analysis of life-science data  .